ปัจจัยที่มีผลต่อการมีส่วนร่วมในการปรับปรุงอย่างต่อเนื่อง (ไคเซ็น) ของพนักงานฝ่ายการผลิต บริษัท ทีซีแอล ทอมสัน อิเล็กทรอนิกส์ (ประเทศไทย) จำกัด - เพ็ชร์รื่น อดิเรก; รัชธร พุทธกาล (วารสารศรีนครินทรวิโรฒวิจัยและพัฒนา สาขามนุษยศาสตร์และสังคมศาสตร์, 2011)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อศึกษาถึงปัจจัยที่มีผลต่อการมีส่วนร่วมในการปรับปรุงอย่างต่อเนื่อง(ไคเซ็น) ของพนักงานฝ่ายการผลิต บริษัท ทีซีแอล ทอมสัน อิเล็กทรอนิกส์ (ประเทศไทย) จำกัด โดยศึกษาปัจจัย 5 ด้าน ได้แก่ ด้านส่วนบุคคล ด้านความรู้เกี่ยวกับไคเซ็น ด้านจิตวิทยา (ทัศนคติ แรงจูงใจ ขวัญและกำลังใจ) ด้านการติดต่อสื่อสาร และด้านการรับรู้นโยบายบริษัทในการทำไคเซ็น เพื่อนำผลการวิจัยมาใช้เป็นแนวทางในการจัดทำกิจกรรมการมีส่วนร่วมในการปรับปรุงอย่างต่อเนื่อง (ไคเซ็น) กลุ่มตัวอย่างที่ใช้ในการศึกษาวิจัยครั้งนี้มาจากประชากรระดับปฏิบัติการ จำนวน 814 คน โดยการสุ่มแบบชั้นภูมิของพนักงานบริษัท ทีซีแอล ทอมสัน อิเล็กทรอนิกส์ (ประเทศไทย) จำกัด ได้กลุ่มตัวอย่าง จำนวน 281 คน การเก็บรวบรวมข้อมูลจากแบบสอบถามและวิเคราะห์ข้อมูลโดยใช้โปรแกรมสำเร็จรูปในการคำนวณค่าสถิติ ได้แก่ ค่าร้อยละ ความถี่ ค่าเฉลี่ย ค่าเบี่ยงเบนมาตรฐาน การทดสอบค่าที ทดสอบความแตกต่างเป็นรายคู่ใช้วิธี LSD การวิเคราะห์ความแปรปรวนทางเดียว และค่าสัมประสิทธิ์สหสัมพันธ์ของเพียร์สัน ผลการวิจัยพบว่า การมีส่วนร่วมในการปรับปรุงอย่างต่อเนื่อง (ไคเซ็น) ของพนักงานฝ่ายการผลิต อยู่ในระดับปานกลาง (ค่าเฉลี่ย 2.82) โดยพนักงานมีความรู้เกี่ยวกับไคเซ็น อยู่ในระดับสูง (ร้อยละ 91.50) มีทัศนคติ แรงจูงใจ และมีขวัญและกำลังใจต่อการมีส่วนร่วมในการปรับปรุงอย่างต่อเนื่อง (ไคเซ็น) อยู่ในระดับดี (ค่าเฉลี่ย 3.52, 3.74 และ 3.44 ตามลำดับ) มีการติดต่อสื่อสารต่อการมีส่วนร่วมในการปรับปรุงอย่างต่อเนื่อง (ไคเซ็น) ในระดับปานกลาง (ค่าเฉลี่ย 2.59) และมีการรับรู้นโยบายบริษัทต่อการมีส่วนร่วมในการปรับปรุงอย่างต่อเนื่อง (ไคเซ็น) อยู่ในระดับดี (ค่าเฉลี่ย 3.65) ผลการทดสอบทางสถิติเป็นดังนี้ 1. ปัจจัยด้านส่วนบุคคล ประกอบด้วย เพศ อายุ สถานภาพสมรส ระดับการศึกษา ประสบการณ์ทำงาน รายได้เฉลี่ยต่อเดือน และการฝึกอบรมเกี่ยวกับไคเซ็นที่แตกต่างกันมีผลต่อการมีส่วนร่วมในการปรับปรุงอย่างต่อเนื่อง (ไคเซ็น) ของพนักงานฝ่ายการผลิตไม่แตกต่างกัน 2. ปัจจัยด้านความรู้เกี่ยวกับไคเซ็นที่แตกต่างกันมีผลต่อการมีส่วนร่วมในการปรับปรุงอย่างต่อเนื่อง (ไคเซ็น) ของพนักงานฝ่ายการผลิต ไม่แตกต่างกัน 3. ปัจจัยด้านจิตวิทยา ในด้านทัศนคติไม่มีความสัมพันธ์กับการมีส่วนร่วมในการปรับปรุงอย่างต่อเนื่อง (ไคเซ็น) ของพนักงานฝ่ายการผลิต 4. ปัจจัยด้านจิตวิทยา ในด้านแรงจูงใจมีความสัมพันธ์ในทิศทางเดียวกันกับการมีส่วนร่วมในการปรับปรุงอย่างต่อเนื่อง (ไคเซ็น) ของพนักงานฝ่ายการผลิต ที่ระดับนัยสำคัญทางสถิติ 0.01 5. ปัจจัยด้านจิตวิทยา ในด้านขวัญและกำลังใจมีความสัมพันธ์ในทิศทางเดียวกันกับการมีส่วนร่วมในการปรับปรุงอย่างต่อเนื่อง (ไคเซ็น) ของพนักงานฝ่ายการผลิต ที่ระดับนัยสำคัญทางสถิติ 0.01 6. ปัจจัยด้านการติดต่อสื่อสารมีความสัมพันธ์ในทิศทางเดียวกันกับการมีส่วนร่วมในการปรับปรุงอย่างต่อเนื่อง (ไคเซ็น) ของพนักงานฝ่ายการผลิต ที่ระดับนัยสำคัญทางสถิติ 0.01 7. ปัจจัยด้านการรับรู้นโยบายบริษัทในการทำไคเซ็นมีความสัมพันธ์ในทิศทางเดียวกันกับการมีส่วนร่วมในการปรับปรุงอย่างต่อเนื่อง (ไคเซ็น) ที่ระดับนัยสำคัญทางสถิติ 0.01 คำสำคัญ: การปรับปรุงอย่างต่อเนื่อง ไคเซ็น ทัศนคติ แรงจูงใจ ขวัญและกำลังใจ The objectives of this research were to study the factors affecting employees’ participation in continual improvement (Kaizen) in operation department of TCL Thomson Electronics (Thailand) Co.,Ltd. To study from five variables included the demographic factor, the knowledge on the Kaizen factor, the psychological factor: attitude, motivation and morale, the communication factor and perception of the company’s policy factor of the participation in continual improvement (Kaizen). The sample group of research from employees of TCL Thomson Electronics (Thailand) Co.,Ltd. was 814 employees by stratified sampling. The sampling group was 281 employees, a questionnaire was used to gather data and the data analysis was processed, through the software package to find out Percentage, Frequency, Mean, Standard Deviation, Independent t-test, the pair difference is analyzed by using LSD, One way Analysis of Variance, and Pearson Product Moment Correlation Coefficient. The results of research found that the employee’s participation in continual improvement (Kaizen) was at the moderate level (Average Mean 2.82). The employees were knowledge at the high level about the Kaizen (91.50%). Their attitude, motivation and morale about the participation in continual improvement (Kaizen) were at the good level (Average Mean 3.52, 3.74 and 3.44 respectively). Communication was the participation in continual improvement (Kaizen) at the moderate level (Average Mean2.59). Their perception of the company’s policy in the participation in continual improvement (Kaizen) was at the good level (Average Mean 3.65). The results of statistical test were found as follows: 1. The finding indicated that a different level of employee’s the participation in continual improvement (Kaizen) in operation department with the demographic factor include gender, age, marital status, educational level, experience of work, average income per month and Kaizen training course were indifferent. 2. The finding indicated that a different level of employees’ the participation in continual improvement (Kaizen) in operation department with the knowledge on the Kaizen factor was indifferent. 3. Psychological factor in attitude was not related to the participation on employees’ the participation in continual improvement (Kaizen) in operation department. 4. Psychological factor in motivation was related to the participation on employees’ the participation in continual improvement (Kaizen) in operation department at the 0.01 statistical significant level, with the same direction. 5. Psychological factor in morale was related to the participation on employees’ the participation in continual improvement (Kaizen) in operation department at the 0.01 statistical significant level, with the same direction. 6. Communication factor was related to the participation on employees’ the participation in continual improvement (Kaizen) in operation department at the 0.01 statistical significant level, with the same direction. 7. Perception of the company’s policy factor was related to the participation on employees’ the participation in continual improvement (Kaizen) in operation department at the 0.01 statistical significant level, with the same direction. Keywords: Continual Improvement, Kaizen, Attitude, Motivation, Morale